Global investment targets for malaria control and elimination between 2016 and 2030. Issue 2 (30th May 2017) - Patouillard, Edith; Griffin, Jamie; Bhatt, Samir; Ghani, Azra; Cibulskis, Richard
Abstract : Background: Access to malaria control interventions falls short of universal health coverage. The Global Technical Strategy for malaria targets at least 90% reduction in case incidence and mortality rates, and elimination in 35 countries by 2030. The potential to reach these targets will be determined in part by investments in malaria. This study estimates the financing required for malaria control and elimination over the 2016–2030 period. Methods: A mathematical transmission model was used to explore the impact of increasing intervention coverage on burden and costs. The cost analysis took a public provider perspective covering all 97 malaria endemic countries and territories in 2015. All control interventions currently recommended by the WHO were considered. Cost data were sourced from procurement databases, the peer-reviewed literature, national malaria strategic plans, the WHO-CHOICE project and key informant interviews. Results: Annual investments of 6.4 billion (95% uncertainty interval (UI 4.5–9.0 billion)) by 2020, 7.7 billion (95% UI 5.4–10.9 billion) by 2025 and 8.7 billion (95% UI 6.0–12.3 billion) by 2030 will be required to reach the targets set in the Global Technical Strategy. These are equivalent to annual investment per person at risk of malaria of US3.90 by 2020, US4.30 by 2025 and US4.40 by 2030, compared with US2.30 if interventions were sustained at current coverage levels. The 20 countries with the highest burden in 2015 will require 88% of the total investment. Conclusions: Given the challenges in increasing domestic and international funding, the efficient use of currently available resources should be a priority.